3
$\begingroup$

compute the summation

$$\sum_ {n=1}^\infty \frac{2n-1 }{2\cdot4\cdots(2n)}= \text{?}$$

My attempts : i take $a_n =\frac{2n-1}{2\cdot4\cdots(2n)}$

Now

\begin{align} & = \frac{2n}{2\cdot4\cdot6\cdots2n} -\frac{1}{2\cdot4\cdot6\cdots2n} \\[10pt] & =\sum_ {n=1}^\infty \left(\frac{2n}{2\cdot4\cdot6\cdots2n} -\frac{1}{2\cdot4\cdot6\cdots2n}\right) \\[10pt] & =\sum_ {n=1}^\infty \left(\frac{1}{1\cdot2\cdot3\cdots(n-1)} -\frac{1}{2(1\cdot2\cdot3\cdots n}\right) \\[10pt] & =\sum_ {n=1}^\infty \left(\frac{1}{(n-1)!} - \frac{1}{2}\sum_ {n=2}^\infty \frac{1}{n!}\right) \\[10pt] & = e - \frac{1}{2} (e- 1)= \frac{1}{2}(e+1) \end{align}

Is it correct ???

if not correct then any hints/solution will be appreciated..

thanks in advance

$\endgroup$
2
$\begingroup$

It is wrong since $$ 2\times 4\times 6\times\dotsb (2n)=2^n n!\quad (n\geq 1). $$ Write $$ \sum_{n=1}^\infty\frac{2n-1}{2^n n!}=\sum_{n=1}^\infty\frac{1}{2^{n-1}(n-1)!}-\sum_{n=1}^\infty\frac{(1/2)^n}{n!} =\sum_{n=0}^\infty\frac{(1/2)^n}{n!}-\sum_{n=1}^\infty \frac{(1/2)^n}{n!}=1. $$ Note that we don't need to know the value of the intermediate sums.

$\endgroup$
  • 1
    $\begingroup$ Why did you change $$\sum_ {n=1}^\infty \frac{2n-1 }{2\cdot4\cdots(2n)}= \text{?}$$ to $\sum_ {n=1}^{\infty} \frac{2n-1 }{2.4........(2n)}= ? \qquad$ $\endgroup$ – Michael Hardy Aug 4 '18 at 15:44
2
$\begingroup$

For $n\ge1,$$$\dfrac{2n-1}{2^n n!}=\dfrac1{2^{n-1}(n-1)!}-\dfrac1{2^nn!}=f(n-1)-f(n)$$

where $f(m)=\dfrac1{2^mm!}$

Can you recognize the Telescoping nature and the surviving term(s) of the summation?

$\endgroup$
2
$\begingroup$

Using telescopic approach with$$a_n=\dfrac{1}{2\cdot4\cdot6\cdot\cdots\cdot2n}$$we have $$S=\sum_{n=1}^{\infty}{a_n-a_{n-1}}=1$$

$\endgroup$
2
$\begingroup$

You made a mistake after this line $$\sum_ {n=1}^{\infty}(\frac{2n}{2.4.6........2n} -\frac{1}{2.4.6........2n})$$ You simplified numerator and denominator by $2n$ but then $$\sum_ {n=1}^{\infty}(\frac{1}{2.4.6........2(n-1)} -\frac{1}{2.4.6........2n})$$

You have at the denominator $$2^nn!$$ So that $$\sum_ {n=1}^{\infty}\frac{2n}{2^nn!}=\sum_ {n=1}^{\infty}\frac{1}{2^{n-1}(n-1)!}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.